Integrative bioinformatics analysis the clinical value of KMT5A in different subtypes of lung cancer. (February 2022) - Liu, Shanshan; Tian, Wenjuan; Li, Burong
Abstract: To combat cancer disease, The Cancer Genome Atlas (TCGA) collects a large amount of information through high-throughput genome analysis technology. At present, there are only few treatments available for lung squamous cell carcinoma (LUSC). Although lysine methyltransferase 5A (KMT5A) is considered as a new biomarker for LUSC, its functionalities needs to be confirmed clinically in lung adenocarcinoma (LUAD). Therefore, in the current investigation we obtained the expression data of KMT5A in LUSC and LUAD by TCGA database. This study evaluated the prognostic value of KMT5A expression in LUAD and LUSC, and discussed the relevant biological pathways of KMT5A involved in the pathogenesis of LUAD and LUSC. KMT5A was highly expressed in LUAD and LUSC cancer tissues. The overall survival analysis revealed that the prognosis of high expression group was poor for LUAD, but was opposite in LUSC. In LUAD, the expression of KMT5A was significantly correlated with age (P = 0.029), gender (P = 0.001) and m (P = 0.042). Logistic regression showed that gender was significantly correlated with poor prognosis of LUAD (P = 0.00175). Multivariate analysis of Cox proportional hazards model exhibited that KMT5A risk ratio (HR) was 0.97, 95% confidence interval (CI), 0.94–1.0, P = 0.026. Age (P = 0.044), t (P = 0.031), m (P = 0.047) were the independent prognostic factors of LUSC patients, while the stage was the independent prognostic factor of LUAD (P < 0.001). Genome enrichment analysis presented that LUSC was differentially enriched with antigen processing and presentation, cell adhesion molecules, cytokine receptor interaction, ECM receptor interaction, etc. LUAD was differentially enriched with apoptosis, cancer pathway, vascular endothelial growth factor signaling pathway and wnt signaling pathway. Overall, this study presented the clinical value of KMT5A in LUSC and LUAD and suggested the possible pathways involved. Graphical Abstract: ga1 Highlights: KMT5A has not been analyzed and verified by large databases in previous lung cancer studies. Bioinformatics analysis showed that KMT5A had different effect on the survival rate of LUSC and LUAD. KMT5A showed different results in the clinical analysis of LUSC and LUAD. Gene enrichment analysis showed that KMT5A was involved in different pathways in LUSC and LUAD.